COCRYSTAL OF ATORVASTATIN CALCIUM – MALONIC ACID - Yudi Wicaksono; Budipratiwi Wisudyaningsih; Tri Agus Siswoyo (UPT Penerbitan Universitas Jember)
Cocrystal is a relatively new solid form of activepharmaceutical ingredient that offers an alternativeplatform in improving physicochemical properties ofactive pharmaceutical ingredients Padrela et al.,2009; Mashhadi et al., 2004. Cocrystal is defined asa stoichiometric multi-component system connectedby non-covalent interactions where all thecomponents neutral and solid under ambientconditions Thakuria et al., 2013. Cocrystal can beconstructed through interaction hydrogen bonding,pi-stacking, and van der Waals forces  Mashhadi etal., 2004. A pharmaceutical cocrystal is composed ofan API and an appropriate coformer as carboxylicacids and amides Qiao et al., 2011.Cocrystallization of active pharmaceutical ingredientis an opportunity for enhancement of importantphysiochemical properties of an activepharmaceutical ingredient without changing itsmolecular structure Maeno et al., 2014.Atorvastatin Calcium (AC), ([(R-(R*,R*)]-2-(4-fluorophenyl)-beta, delta-dihydroxy-5-(1-methylethyl)-3-phenyl-4-[(phenylamino)carbonyl]-1H-pyrrole-1-heptanoic acid), calcium salt (2:1)trihydrate ([C33H34FN2O5]2Ca.3H2O), is considered asone of the most effective of synthetic lipid loweringagent Shete et al., 2010. The drug is orally used toreduce of total cholesterol, low density lipoproteinand triglycerides Anwar et al., 2011. There are 42crystalline structures of AC Shayanfar et al., 2013.However, chance to create AC into another crystalstructure to improving physicochemical properties ofAC is still fully open Chadha et al., 2012.In the present study, we explored cocrystallization ofAC by solvent evaporation method. This study aimedto confirm whether AC was able to form cocrystalwith malonic acid (MA) as coformer. AC-MAcocrystal was prepared by solvent evaporationmethod by using methanol as solvent.Characterization of cocrystal was done by powder Xraydiffractometry (PXRD), differential scanningcalorimetry (DSC), fourier transform infrared (FTIR)spectroscopy and scanning electron microscopy(SEM).